The haunted season [large type] : a Max Tudor novel - Malliet, G. M., 1951- (Malliet, G. M., 1951- Max Tudor novel., 2016)
Something sinister is afoot at Totleigh Hall, the showcase of the sleepy English village of Nether Monkslip. Lord and Lady Baaden-Boomethistle have been in residence for some weeks now, and the villagers are hoping for a return to the days when the lord of the manor sprinkled benefits across the village like fairy dust. But a sudden grisly death intervenes, and Max Tudor's talent for sorting through clues is once again called into play.